1999
DOI: 10.1116/1.590908
|View full text |Cite
|
Sign up to set email alerts
|

Integration methodology of chemical vapor deposition TiN, chemical vapor deposition W and W chemical mechanical planarization for sub-quarter micron process application

Abstract: Chemical vapor deposition ͑CVD͒ W plugs have been widely used for device metallization with excellent conformity in small contacts/vias with high aspect ratio ͓J. E. J. Schmitz, Chemical Vapor Deposition of Tungsten and Tungsten Silicides ͑Noyes, 1991͔͒. However, some unexpected plug fill such as plug loss and key hole exposing post tungsten chemical mechanical planarization ͑WCMP͒ still happened while going to smaller plug size and using metalorganic chemical vapor deposition ͑MOCVD͒ TiN barrier. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…With the extension of exposure time, the corrosion rate of the two kinds of steel decreases, which is due to the protective effect of surface corrosion products on the matrix. This phenomenon is consistent with the research results of Wu et al [ 19 ] and others. [ 16,17 ] In different periods, the corrosion rate of Sb‐added steel is lower than that of Sb‐free steel.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…With the extension of exposure time, the corrosion rate of the two kinds of steel decreases, which is due to the protective effect of surface corrosion products on the matrix. This phenomenon is consistent with the research results of Wu et al [ 19 ] and others. [ 16,17 ] In different periods, the corrosion rate of Sb‐added steel is lower than that of Sb‐free steel.…”
Section: Resultssupporting
confidence: 94%
“…In 2004, Nippon Steel Corporation first found [ 18 ] that adding an appropriate amount of Sb into Cu‐containing steel could promote the formation of Cu 2 Sb film, inhibit electrochemical anodic and cathodic reactions, and significantly improve the corrosion resistance of low‐alloy steel in sulfuric acid and hydrochloric acid. Wu et al [ 19 ] developed a new type of low‐alloy steel to improve its acid dew point corrosion resistance in high‐temperature and acidic environments. The results showed that the addition of Sb accelerated the redeposition of Cu during the corrosion process and then formed a rich layer of Cu and Sb on the inside of the surface film to improve the acidic corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For tungsten deposition, it is conducted at the temperature range of 400-425 -C in a single wafer reactor. WF 6 /SiH 4 ratio variation is controlled for plugfilling completion [9]. By adjusting above two CVD TiN parameters, plasma treatment power and treated time, we analyzed the effects of the tungsten film on the grain size and orientation.…”
Section: Methodsmentioning
confidence: 99%
“…These changes not only become more critical for VIA filling and resistance, but also make the influences on the quality of tungsten film, and even change the seam formation in the small contact VIA size. For WCVD, the seam formation is accompanied with the subsequent nucleation and bulk deposition process on different VIA sidewalls [9]. But the seam formation beyond 100 nm technology is dependent on the VIA size and becomes critical in the VIA resistance and the quality of VIA gapfilling.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Therefore, the desulfurizer waste and the low efficiency of desulfurization are critical problems in the desulphurization process using injection magnesium method. [3][4][5] The injected bubbles are large in size and concentrate on the partial space around the nozzle when the conventional injection method is applied. The injected bubbles go up rapidly in the hot metal without adequate contacting with the hot metal, which results in the desulfurizer waste and low desulfurization efficiency in the deep desulphurization process.…”
Section: Introductionmentioning
confidence: 99%